A new quantum gas apparatus for ultracold mixtures of K and Cs and KCs ground-state molecules. Issue 18 (10th October 2016) - Gröbner, M.; Weinmann, P.; Meinert, F.; Lauber, K.; Kirilov, E.; Nägerl, H.-C.
Abstract : We present a new quantum gas apparatus for ultracold mixtures of K and Cs atoms and ultracold samples of KCs ground-state molecules. We demonstrate the apparatus' capabilities by producing Bose–Einstein condensates of 39 K and 133 Cs in a manner that will eventually allow sequential condensation within one experimental cycle, precise sample overlap and magnetic association of atoms into KCs molecules. The condensates are created independently without relying on sympathetic cooling. Our approach is universal and applicable to other species combinations when the two species show dramatically different behavior in terms of loss mechanisms and post laser cooling temperatures, i.e. species combinations that make parallel generation of quantum degenerate samples challenging. We give an outlook over the next experiments involving e.g. sample mixing, molecule formation and transport into a science chamber for high-resolution spatial imaging of novel quantum-many body phases based on K–Cs.